PEMANTAPAN NILAI-NILAI KEBANGSAAN BAGI ETNIS TIONGHOA - Kurnia Setiawan; Ninawati Lihardja; Meiske Yunithree (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2020)
Pancasila values need to be understood and practiced in everyday life. The INTI (Indonesian Chinese) Association conducts training on "Consolidating Pancasila Values (Taplai)". The joint Taplai activity of Chinese organizations was the first to be held. This study wanted to find out whether the Taplai Training could increase the knowledge, understanding and nationalistic attitudes of the training participants. The socialization of the Taplai activity was conducted in front of 13 organizations from various Chinese organizations, businessmen, professionals, and several non-Chinese representatives. The research used a mixed method of quantitative and qualitative through distributing questionnaires pre-test and post-test, observation and interviews. Based on the results of data collection through questionnaires and interviews from 91 participants, it can be concluded that the Taplai training can increase knowledge about the values of Pancasila and foster a sense of nationality. In general, all subjects understood national values that refer to the four pillars, namely Pancasila, UUD 1945, Bhinneka Tunggal Ika and NKRI, several participants who were interviewed all gave positive testimonies about the experience and benefits of the Taplai training for them. Nilai-nilai Pancasila perlu dipahami dan diamalkan dalam kehidupan sehari-hari, Perhimpunan INTI (Indonesia Tionghoa) melaksnakan pelatihan “Pemantapan Nilai-Nilai Pancasila (Taplai)”. Kegiatan Taplai gabungan organisasi Tionghoa merupakan yang pertama kali diadakan. Penelitian ini ingin mengetahui apakah Pelatihan Taplai dapat meningkatkan pengetahuan, pemahaman dan sikap nasionalisme peserta pelatihan. Sosialisasi kegiatan Taplai di hadapan 13 organisasi yang berasal dari berbagai organisasi Tionghoa, pengusaha, profesional, dan beberapa perwakilan non Tionghoa. Penelitian menggunakan metode campuran antara kuantitatif dan kualitatif melalui penyebaran kuesioner pre-test dan post-test, observasi serta wawancara. Berdasarkan hasil pengumpulan data melalui kuesioner dan wawancara dari 91 peserta, dapat disimpulkan pelatihan Taplai dapat meningkatkan pengetahuan tentang nilai-nilai Pancasila dan menumbuhkan rasa kebangsaan. Pada umumnya semua subyek memahami tentang nilai-nilai kebangsaan yang mengacu pada empat pilar, yaitu Pancasila, UUD 1945, Bhinneka Tunggal Ika dan NKRI, beberapa peserta yang diwawancara semua memberikan kesaksian yang positif tentang pengalaman dan manfaat pelatihan Taplai bagi mereka.